Tikio (TikTok App Educational Video) Based on the Character Education of Newton’s Laws Concepts Preferred to Learning for Generation Z - Risky Januar Syah; Siti Nurjanah; Veneranda Putri Andri Mayu (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
The massive tendency of Generation Z activities on social media should be thought as opportunities for interaction from the education segment. Intake of educational content based on character education is not only in conventionally implemented that can touch the Generation Z, but also in the whole process of learning including the learning media. The purpose of this paper is to offer alternative learning media in the form of educational videos that are interesting, sticky, and creative for students through the contemporary platform, such as TikTok. TikTok application comes with a popular trend that the majority of users are Generation Z. Based on its features that support to produce interesting audio and video learning, it can streamline the learning process. The interesting and entertaining learning nuance of this application is useful for essential and abstract concepts such as Newton's laws to create an interactive learning process in accordance with the characteristics of students.